A great duty : Canadian responses to modern life and mass culture in Canada, 1939-1967 - Kuffert, L. B. (Leonard B.) (McGill-Queen's University Press, 2003)
Annotation In A Great Duty L.B. Kuffert shows that the history of Canadian culture from the war to Canada's centenary is much richer and more complex than has previously been recognized. He looks at the responses of cultural critics to such topics as war, reconstruction, science, conformity, personality, and commemoration, catching outspoken observers in the act of synthesizing new interpretations of the contemporary world and protesting the dominance of mass-produced entertainment.
Keywords: Popular culture -- Canada -- History -- 20th century.; Canada -- Civilization -- 20th century.; Culture populaire -- Canada -- Histoire -- 20e siècle.; Canada -- Civilisation -- 20e siècle.; POLITICAL SCIENCE -- Public Policy -- Cultural Policy.; SOCIAL SCIENCE -- Anthropology -- Cultural.; SOCIAL SCIENCE -- Popular Culture.; HISTORY -- Canada -- General.; Civilization; Popular culture; Canada; 1900-1999; History